# Solve the given expression to obtain the value of x:

$\dfrac{{2x + 7}}{3} = \left( {x + 4} \right)$

Last updated date: 19th Mar 2023

•

Total views: 304.8k

•

Views today: 2.86k

Answer

Verified

304.8k+ views

Hint – In this question we need to solve for the value of x, use cross multiplication along with a simple simplification technique to solve the given equation for the value of x.

Complete step-by-step answer:

Given equation is

$\dfrac{{2x + 7}}{3} = \left( {x + 4} \right)$

Now the given equation is also written as

$\dfrac{{2x + 7}}{3} = \dfrac{{x + 4}}{1}$

Now apply cross multiplication method (i.e. (2x + 1) is multiplied by 1 and (x + 4) is multiplied by 3)

$ \Rightarrow 1\left( {2x + 7} \right) = 3\left( {x + 4} \right)$

Now simplify the above equation we have,

$ \Rightarrow 2x + 7 = 3x + 12$

Now shifting the variables i.e. 3x to L.H.S and 7 to R.H.S we have

$ \Rightarrow 2x - 3x = 12 - 7$

$ \Rightarrow - x = 5$

Now multiply by -1 we have,

$ \Rightarrow x = - 5$

So, this is the required solution of the given equation.

So, this is the required answer.

Note – Whenever we face such types of problems the key concept is simply to use basic techniques of cross multiplication and subtraction of terms with the same variables. This concept will help you get on the right track to reach the answer.

Complete step-by-step answer:

Given equation is

$\dfrac{{2x + 7}}{3} = \left( {x + 4} \right)$

Now the given equation is also written as

$\dfrac{{2x + 7}}{3} = \dfrac{{x + 4}}{1}$

Now apply cross multiplication method (i.e. (2x + 1) is multiplied by 1 and (x + 4) is multiplied by 3)

$ \Rightarrow 1\left( {2x + 7} \right) = 3\left( {x + 4} \right)$

Now simplify the above equation we have,

$ \Rightarrow 2x + 7 = 3x + 12$

Now shifting the variables i.e. 3x to L.H.S and 7 to R.H.S we have

$ \Rightarrow 2x - 3x = 12 - 7$

$ \Rightarrow - x = 5$

Now multiply by -1 we have,

$ \Rightarrow x = - 5$

So, this is the required solution of the given equation.

So, this is the required answer.

Note – Whenever we face such types of problems the key concept is simply to use basic techniques of cross multiplication and subtraction of terms with the same variables. This concept will help you get on the right track to reach the answer.

Recently Updated Pages

If abc are pthqth and rth terms of a GP then left fraccb class 11 maths JEE_Main

If the pthqth and rth term of a GP are abc respectively class 11 maths JEE_Main

If abcdare any four consecutive coefficients of any class 11 maths JEE_Main

If A1A2 are the two AMs between two numbers a and b class 11 maths JEE_Main

If pthqthrth and sth terms of an AP be in GP then p class 11 maths JEE_Main

One root of the equation cos x x + frac12 0 lies in class 11 maths JEE_Main

Trending doubts

What was the capital of Kanishka A Mathura B Purushapura class 7 social studies CBSE

Difference Between Plant Cell and Animal Cell

Write an application to the principal requesting five class 10 english CBSE

Ray optics is valid when characteristic dimensions class 12 physics CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

Tropic of Cancer passes through how many states? Name them.

Write the 6 fundamental rights of India and explain in detail

Write a letter to the principal requesting him to grant class 10 english CBSE

Name the Largest and the Smallest Cell in the Human Body ?